The effect of principal transformational leadership on teacher innovative behavior: the moderator role of uncertainty avoidance and the mediated role of the sense of meaning at work - Bao, Yuangen (Frontiers in Education, 2024)
Introduction Given the rapid technological advancements and increasing global uncertainties, principals’ promoting teacher innovative behavior (TIB) is fundamental for schools to enhance effectiveness and achieve sustainable competitive growth. However, previous research on the impact of principal transformational leadership (PTL) on TIB has yielded conflicting results. Drawing upon social cognitive theory and leadership substitution theory, this study constructs a model to elucidate the mediating role of teachers’ sense of meaning in work (TMW) between PTL and TIB, as well as the moderating role of teachers’ uncertain avoidance (TUA) in mainland China. Methods The model was examined in Chinese primary and secondary schools, with data gathered in January and July 2023. A total of 295 primary and secondary school teachers participated in this research. With Hayes’ PROCESS macro, we examined all the direct and indirect paths, including moderated mediation. Results The findings confirm that PTL positively influences TIB, with TMW serving as a mediator in this relationship. Furthermore, TUA moderates both direct and indirect relationships mentioned above. Discussion These findings shed light on the underlying mechanisms through which principal transformational leadership impacts teacher innovative behavior. The implications derived from this conclusion offer valuable managerial insights for principals seeking to promote TIBs.